2020
DOI: 10.1002/jbt.22563
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA PVT1 exacerbates the inflammation and cell‐barrier injury during asthma by regulating miR‐149

Abstract: Background Asthma is a prevailing respiratory disease among children, characterized by allergic airway inflammation, airway remodeling, and airway hyperresponsiveness. Although it is well‐known that long non‐coding RNAs (lncRNAs) are linked to a variety of human diseases and well‐documented, very few studies explore its role in asthma. In this study, we investigate the effects of lncRNA PVT1 on the promotion of airway inflammation and its associated mechanisms. Methods and Materials Human small airway epitheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 26 publications
0
32
0
Order By: Relevance
“…Many studies have found that miRNA is crucial in cell differentiation, proliferation and apoptosis, and is related to many human diseases, such as cancer, chronic obstructive pulmonary disease, and interstitial lung disease, and asthma [ 26–31 ]. MiR-19a expression is dramatically raised in T lymphocytes infiltrated in the airway of asthma, and miR-19a can regulate PTEN, SOCS1 and A20 to cooperatively induce the production of Th2 cytokines [ 29 ]; miR-142-3p takes part in regulating the multiplication and differentiation of airway smooth muscle cells in asthma by inhibiting WNT signaling pathway [ 30 ]; miR-149 overexpression can inhibit inflammatory cytokines’ expressions in HSAECs induced by PAF, and alleviate the barrier damage of epithelial cells [ 31 ]. Here we reported that miR-146a-5p expression was declined in the blood samples of asthma individuals and PAF-stimulated HSAECs; miR-146a-5p overexpression can inhibit the secretion of inflammatory cytokines in HSAECs treated by PAF, alleviate the barrier damage of epithelial cells, and effectively inhibit the apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have found that miRNA is crucial in cell differentiation, proliferation and apoptosis, and is related to many human diseases, such as cancer, chronic obstructive pulmonary disease, and interstitial lung disease, and asthma [ 26–31 ]. MiR-19a expression is dramatically raised in T lymphocytes infiltrated in the airway of asthma, and miR-19a can regulate PTEN, SOCS1 and A20 to cooperatively induce the production of Th2 cytokines [ 29 ]; miR-142-3p takes part in regulating the multiplication and differentiation of airway smooth muscle cells in asthma by inhibiting WNT signaling pathway [ 30 ]; miR-149 overexpression can inhibit inflammatory cytokines’ expressions in HSAECs induced by PAF, and alleviate the barrier damage of epithelial cells [ 31 ]. Here we reported that miR-146a-5p expression was declined in the blood samples of asthma individuals and PAF-stimulated HSAECs; miR-146a-5p overexpression can inhibit the secretion of inflammatory cytokines in HSAECs treated by PAF, alleviate the barrier damage of epithelial cells, and effectively inhibit the apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Fabp4 inhibitors suppress inflammation and oxidative stress in murine and cell models of acute lung injury [ 23 ], and suppression of Fabp4 protects against rhabdomyolysis-induced acute kidney injury [ 24 ]. In chronic obstructive pulmonary disease patients, the PVT1 expression positively correlated with the GOLD stage and levels of TNF- α , IL-6, IL-8, and IL-17 [ 25 ]; PVT1 exacerbates the inflammation and cell-barrier injury during asthma by regulating miR-149 [ 26 ]. These findings suggested that Fabp4 and PVT1 might play the role in the therapeutic potential of MSCs in phosgene-induced ALI, and we will research the potential role of them in the phosgene-induced ALI in the following research.…”
Section: Discussionmentioning
confidence: 99%
“…25 PVT1 knockdown inhibited the levels of inflammatory factors in asthma. 11 Altogether, lncRNA PVT1 and lncRNA PVT1/miR-423-5p axis were associated with increased severity of BA while miR-423-5p was negatively correlated with BA severity.…”
Section: Fundingmentioning
confidence: 91%
“…9,10 Based on the existing study, lncRNA plasmacytoma variant translocation 1 (PVT1) might be important in asthma and lncRNA PVT1 exacerbates inflammation and cell-barrier injury during asthma by modulating miR-149. 11 According to the study of Austin et al, PTV1 was upregulated in the primary airway smooth muscle cells of patients with asthma and PVT1 expression might affect the proliferation of airway smooth muscle cells and the release of interleukin (IL)-6. 12 However, the expression of lncRNA PVT1 in the serum of BA patients and whether lncRNA PTV1 could be used for BA diagnosis and treatment require further investigation.…”
Section: Introductionmentioning
confidence: 99%